Single arterial access closure of post‐infarction ventricular septal defect: A case series. Issue 1 (7th December 2022) - Doost, Ata; Chilmeran, Ahmed; Gomes, Arionilson; Dworakowski, Rafal; Eskandari, Mehdi; MacCarthy, Philip; Cockburn, James; Byrne, Jonathan; Hildick‐Smith, David
Abstract: Background: Post‐infarction ventricular septal defect (PIVSD) carries a very poor prognosis. Surgical repair offers reasonable outcomes in patients who survive the initial healing period. Percutaneous device implantation remains a potentially effective earlier alternative. Methods and Results: From March 2018 to May 2022, 11 trans‐arterial PIVSD closures were attempted in 9 patients from two centers (aged 67.2 ± 11.1 years; 77.8% male). Two patients had a second procedure. Myocardial infarction was anterior in four patients (44.5%) and inferior in five cases (55.5%). Devices were successfully implanted in all patients. There were no major immediate procedural complications. Immediate shunt grade postprocedure was significant (11.1%), minimal (77.8%), or none (11.1%). Median length of stay after the procedure was 14.8 days. Five patients (55%) survived to discharge and were followed up for a median of 605 days, during which time no additional patients died. Conclusion: Single arterial access for percutaneous closure of PIVSD is a good option for these extremely high‐risk patients, in the era of effective large‐bore arterial access closure. Mortality remains high, but patients who survive to discharge do well in the longer term.